THE DIAGNOSING THE PATHOLOGY OF INTER-PARTY POLITICS IN TIMOR LESTE IN HONNETH'S POLITICS OF RECOGNITION - Guterres, Elidio Agusto (Ridwan Institute, 2024)
This paper presents a philosophical analysis of inter-party conflict through the lens of Axel Honneth's theory of recognition. The analysis reveals that the root cause of conflict is not merely linguistic or communicative failure (as per Habermas' theory), but a lack of mutual recognition among conflicting parties. The article offers a deeper understanding of political pathology, highlighting the root causes of political conflict. Specifically, the article proposes that the conflict between parties in Timor Leste during the struggle period can be said to be a communal political conflict, which occurred due to the absence of interparty recognition as the people of Timor leste who were struggling against imperialism and colonialism. This would allow for a broader understanding of the ways in which the recognition theory can be adapted to various cultural and political contexts, identifying best practices for conflict resolution and sustainable peace-building efforts in other nations with similar historical struggles.